O pojmowaniu infotainmentu i nadmiernej rozrywkowości mediów masowych we współczesnym medioznawstwie - Fras, Janina (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2013)
The excessive focus on entertainment in the content of the modern mass media has become the subject of academic reflection in Poland over the last decade. In the West this issue has been discussed for at least thirty years. Out of the various concepts that serve the purpose of describing and analyzing the focus on entertainment in the mass media the author focuses on the concept of infotainment, borrowed from American English; the meaning and scope of this concept in academic and journalistic texts is analyzed. It is indicated that the concept has a limited explanatory value when taken over without its cultural and linguistic context, and it is particularly useless as the name of a genre, used instead of the news. Discussing contemporary academic reflections on the focus on entertainment in the mass media and their content, three main currents are indicated and briefly described: the functional, historical and critically-discursive; the issue of the focus on entertainment of professional journalists is also addressed.